(untitled) (Journal of the College of Basic Education, 2019)
In this work, a colloidal suspension aqueous solution of Au/Ag composite nanoparticles by pulsed laser ablation method was obtained. Q-switched Nd:YAG, λ=1064nm, 532nm10 ns pulse duration and E=100-900 mJ and by using pure Ag and Au metal plates immersed in pure water. The optical extinction spectra have been obtained in the Plasmon resonance region. The results are supported by X-ray data and transmission electron microscopy. UV-VIS absorption spectra of produced solution show a sharp peak around 400 nm, 525nm indicating the produced Ag and Au nanoparticles respectively with a narrow size ranging from (5 to 45) nm for Ag NPs, (8-55)nm for Au NPs and (10-170)nm for Au/Ag composite NPs with almost spherical shape X-ray data indicate the fcc (face-centered cubic) structure. This work presents the effect of number of pulses on the properties of the prepared Au, Ag and Au-Ag alloy NPs, also included a study of the biomedical effects of Au, Ag, Au-Ag alloy NPs on the activity of Alkaline Phosphatase enzyme in human blood.